Between understanding and appropriation: game-based learning from the perspective of rural teachers - Gonzales-Huamán, Rodrigo (2025)
The incorporation of Game-Based Learning has been promoted as a cornerstone of pedagogical innovation, yet important gaps persist regarding how teachers, especially in rural areas, understand and appropriate this strategy under conditions of scarcity. Guided by this overarching question, the study sought to understand, both theoretically and practically, how primary-school teachers at IE 70022-Collana (Puno - Peru) appropriate the strategy, using a qualitative phenomenological–interpretive approach. Five in-depth interviews were conducted with teachers who had more than twenty-five years of service, and a thematic analysis supported by qualitative coding was applied. Findings reveal: 1) a strong conviction that play is a prerequisite for meaningful learning and a cultural bond; 2) structural constraints (scarce materials, lack of time and weak institutional support) that compel creative adaptation with local resources; and 3) practices of resignification ranging from instrumental appropriation, limited to specific moments, to deep appropriation, where play becomes the organising axis of the curriculum, community identity and classroom socio-emotional well-being. On this basis, a double-helix model is proposed: one strand of “comprehension” (playful beliefs, self-efficacy, prior knowledge) and another of “appropriation” (situated diagnosis, adaptive integration and social legitimation), whose interaction explains the density of pedagogical resignification achieved. The study concludes that genuine transformation of teachers’ thinking depends on both critical reflection and supportive institutional conditions; otherwise, the strategy risks remaining a limited adaptive response.